Can Fraud Diamond Affect Fraud Financial Statement In Sharia Commercial Banks? - Dinnul Alfian Akbar; Fernando Africano; Ridandy Isrodinata (Universitas Muhammadiyah Malang, 2021)
This research aims to obtain empirical evidence of the effect of fraud diamond (pressure as proxied by financial stability, opportunity which is proxied by effective monitoring, rationalization which is proxied by total accruals, and proxied capability by change of directors) on financial statement fraud at Islamic Commercial Banks. The population in this study were banking companies that were on the list of Islamic Commercial Banks. Then the sample was taken using purposive sampling technique. The research used logistic regression because the dependent variable is a dummy variable. The results of this research indicate that the pressure variable has no effect on financial statement fraud. Opportunity variable has a negative effect on financial statement fraud. Then, the rationalization variable has a negative effect on financial statement fraud. And the capability variable has no effect on financial statement fraud. The results of this study are expected to be useful for companies, especially banking, as a material for consideration in preventing fraud on financial statements.